Pelatihan metodologi penelitian sains dan teknologi bagi santri Madrasah Aliyah Negeri Insan Cendekia Lombok Timur - Ardiana Ekawanti Ardiana; Rifana Cholidah Rifana; Rizka Vidya Lestari Rizka; Imam Maksum Al Maliki Imam (INDRA: Jurnal Pengabdian kepada Masyarakat, 2022)
Basic knowledge on scientific method is important for the preparation of scientific papers for student of Madrasah Aliyah Negeri. Since, research methodology was not teached in Madrasah Aliyah curriculum. Writing scientific papers is an activity related to education from elementary school to university level, which teaches rational and empirical thinking by using scientific method. This training was intended to provide knowledge about research methodologies, especially in the fields of science and technology for the preparation of students' final assignments of Madrasah Aliyah Negeri Insan Cendekia East Lombok. The method of activity was by lectures, discussions and guidance for writing research proposal. This activity took place on July 1, 2022 in the Hall of MAN Insan Cendekia, attended by 111 students. This activity consist three session, first is the explanation about material from the lectures, followed by discussion and the last session is mentoring. The students followed the activity enthusiastically marked by so many question in the discussion session about the topic of research and its design.